Rainfall, drought, and irrigation in relation to crop patterns in the volcanic topo sequence of Central Java, Indonesia - Sumani Sumani; Komariah Komariah; Suntoro Suntoro; Mujiyo Mujiyo; Hayat Ullah (Sains Tanah: Journal of Soil Science and Agroclimatology)
The uncertainty in precipitation patterns resulting from climate change may contribute to uncertainties in the growing seasons and productivity of rice and other agricultural commodities. This study aimed to examine the changes in precipitation and cropping patterns across various topographic sequences of volcanic regions in Central Java, Indonesia. Precipitation data from 33 rainfall stations across three topographic sequences (0-400 meters, 400-700 meters, and above 700 meters above sea level, categorized as high, mid, and lowlands, respectively) were analyzed to understand cropping patterns using both quantitative and qualitative methods. The findings revealed that farmers' actual cropping patterns were not primarily influenced by precipitation levels but rather by soil suitability. Moreover, the frequency of drought occurrences, as indicated by the Standardized Precipitation Index (SPI), did not significantly impact cropping patterns or crop yields. Instead, agricultural yields were found to be dependent on irrigation infrastructure rather than precipitation levels. This study sheds light on the importance of adaptation and mitigation strategies to address the adverse impacts of climate change on agricultural management across different topographic sequences.